PENGARUH KETEPATAN SKEDUL PENYUSUNAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) DAN SISTEM PENGENDALIAN INTERN TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN SIAK - Utary Aini; Kirmizi Ritonga; Sem Paulus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Local government performance not separated from the local government budget. The performance of a government can be judged from the budget. One of accuracy in budgeting. And in the implementation of the budget on time, internal control systems are also needed so that everything stays in control. The goal of this research is conducted to explore whether there is empirical evidence about the effect of budget scheduling and internal control system of local government in Siak Regency. The object of this study is Siak regency. This study performed on local government in SKPD Siak Regency with the second, third, and fourth echelon position. Primary data collection method conducted with survey technique by providing questions to respondents by the questionnaire. The result of this study showed that budget scheduling and internal control system had a positive and signifikan effect in performance of local government.Keywords : Budget Scheduling, Internal Control System, Local Government Perormance.